Regulatory Compliance of Indonesian Smart Contracts - Irsyad Noeri; Salsa Nur Ramadhani Hermandasari (Journal of Law, Society and Living Norms, 2025)
This research aims to examine the regulatory compliance aspects of smart contracts within the Indonesian legal system using a Systematic Literature Review (SLR) approach. The review focuses on how smart contracts are recognized and regulated within Indonesia’s legal framework, the challenges related to consumer protection, their compatibility with traditional contract principles, and comparisons with international regulatory standards. From a total of 158 relevant studies, 50 articles were selected based on multi-layered search strategies, citation chaining, and relevance scoring. The findings reveal that while Indonesia has established a normative legal basis for recognizing electronic contracts, significant gaps persist in enforcement, legal clarity, and consumer protection. The implications of this review highlight the need for regulatory reform, the standardization of legal frameworks, and the integration of interdisciplinary approaches to secure the application of smart contracts within Indonesia’s growing digital economy.